Curculigoside Ameliorates Bone Loss by Influencing Mesenchymal Stem Cell Fate in Aging Mice - Wang, Na; Li, Ziyi; Li, Shilun; Li, Yukun; Gao, Liu; Bao, Xiaoxue; Wang, Ke; Liu, Chang; Xue, Peng; Liu, Sijing (Frontiers in Cell and Developmental Biology, 2021)
Senile osteoporosis is characterized by increased bone loss and fat accumulation in marrow. Curculigoside (CCG) is the major bioactive component of Curculigo orchioides which has been used as anti-osteoporosis therapy for elder patients since antiquity. We aimed to investigate the underlying mechanisms by which CCG regulated the bone-fat balance in marrow of aging mice. In our study, CCG treatment was identified to interfere with the stem cell lineage commitment both in vivo and in vitro. In vivo, CCG promoted the transcriptional co-activator with PDZ-binding motif (TAZ) expression to reverse age-related bone loss and marrow adiposity. In vitro, proper concentration of CCG upregulated TAZ expression to increase osteogenesis and decrease adipogenesis of bone marrow mesenchymal stem cells (BMSCs). This regulating effect was discounted by TAZ knockdown or the use of MEK-ERK pathway inhibitor, UO126. Above all, our study confirmed the rescuing effects of CCG on the differential shift from adipogenesis to osteogenesis of BMSCs in aging mice, and provided a scientific basis for the clinical use of CCG in senile osteoporosis.